High-strength heat-resistant aluminum-copper-magnesium alloy and preparation method thereof
By increasing the concentration of Mg elements in aluminum-copper-magnesium alloys, adjusting the Cu/Mg mass ratio, introducing Mn, Zr, Ti and Sc elements, and adopting dual-stage solid solution and aging heat treatment processes, the existing high-strength heat-resistant aluminum-copper-magnesium alloys have been solved, and higher mechanical properties and lower preparation costs have been achieved.
Patent Information
- Application Number
- CN202411927728.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing high-strength heat-resistant aluminum-copper-magnesium alloys have high cost and low strength at room temperature and 300°C high temperatures.
By rationally designing the composition of aluminum-copper-magnesium alloys, increasing the concentration of Mg elements, setting the Cu/Mg mass ratio between 2 and 4, introducing Mn and Zr elements to reduce the diffusion rate of Cu elements, adding refined elements such as Ti and Sc, and adopting a dual-stage solid solution process and aging heat treatment process.
It significantly reduces the preparation cost of the alloy, improves the mechanical properties at room temperature and high temperature of 300℃, and ensures that the alloy still has a high strength and elongation at high temperatures.
Smart Images

Figure CN119800178A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-strength, heat-resistant, lightweight structural casting metal materials, and in particular to a high-strength, heat-resistant aluminum-copper-magnesium alloy and a preparation method thereof. Background Art
[0002] Aluminum alloy is a lightweight, high-strength alloy widely used in aerospace, automobile manufacturing, shipbuilding and other fields. Due to the short-term high-temperature friction environment in the service process of aerospace, high heat resistance requirements are placed on equipment materials. Existing alloy grades such as 201.0 alloy have high room temperature and high temperature strength. It mainly adds Cu elements to form the θ-Al2Cu strengthening phase, and promotes the formation of the Al2Cu high-temperature stable phase Ω through the introduction of Ag elements. However, the Ag element has a high addition cost, and when the service temperature exceeds 250°C, the high-temperature stable phase Ω is replaced by the θ phase, and its strength is difficult to meet the higher requirements for heat resistance of existing aviation and spacecraft structural materials. Therefore, it is urgent to find a casting aluminum alloy material with more cost advantages and high strength and heat resistance. Summary of the invention
[0003] In view of the above analysis, the embodiments of the present invention are intended to provide a high-strength and heat-resistant aluminum-copper-magnesium alloy and a preparation method thereof, which are used to at least solve one of the following problems existing in the existing high-strength and heat-resistant aluminum-copper-magnesium alloy and a preparation method thereof: 1. The existing high-strength and heat-resistant aluminum-copper-magnesium alloy and a preparation method thereof have high alloy cost; 2. The existing high-strength and heat-resistant aluminum-copper-magnesium alloy has low alloy strength at room temperature and at a high temperature of 300°C.
[0004] The purpose of the present invention is mainly achieved through the following technical solutions:
[0005] The invention provides a high-strength heat-resistant aluminum-copper-magnesium alloy. The alloy components are calculated by mass percentage as follows: Cu: 4.5-5.5%, Mg: 1.5-2.5%, Mn: 0.2-1.0%, Ti: 0.1-0.5%, Zr: 0.1-0.5%, Sc: 0.1-0.5%; Fe: 0-0.1%; the balance is aluminum and inevitable impurities.
[0006] Furthermore, the alloy components are calculated by mass percentage as follows: Cu: 4.94-5.12%, Mg: 1.84-2.32%, Mn: 0.41-0.79%, Ti: 0.1-0.25%, Zr: 0.15-0.22%, Sc: 0.3-0.33%; Fe: 0-0.08%; the remainder is aluminum and unavoidable impurities.
[0007] Furthermore, in the alloy component, the mass ratio of Cu / Mg is 2-4.
[0008] The present invention also provides a method for preparing a high-strength heat-resistant aluminum-copper-magnesium alloy, which is used to prepare the aluminum-copper-magnesium alloy, comprising the following steps:
[0009] S1: According to the mass percentage of each element, pure Al, pure Mg, Al-Mn master alloy, Al-Cu master alloy, Al-Ti master alloy, Al-Zr master alloy, and Al-Sc master alloy are weighed as raw materials respectively;
[0010] S2: Smelting starts, adding pure aluminum ingots, Al-Mn master alloys, and Al-Cu master alloys to the resistance furnace, and keeping them warm at the first smelting temperature. After they are molten, Al-Ti master alloys, Al-Zr master alloys, and Al-Sc master alloys are added to continue smelting at the first smelting temperature, and keeping warm. After the temperature drops to the second smelting temperature, a pure magnesium block is pressed in with a pressing spoon;
[0011] S3: After all the alloy elements are added, refining and degassing are carried out, standing and slag removal is carried out;
[0012] S4: casting;
[0013] S5: subjecting the cast alloy to solid solution and aging treatment to obtain a finished alloy product.
[0014] Furthermore, in step S2, the first smelting temperature is 750-800°C, and the holding time is 30-60 minutes.
[0015] Furthermore, in step S2, the second smelting temperature is 700-730°C.
[0016] Furthermore, in step S3, the step of standing is 20-30 minutes.
[0017] Furthermore, in step S4, the casting process is gravity or low-pressure casting, the pouring temperature is 670-690°C, and the mold insulation temperature is 150-200°C.
[0018] Furthermore, in step S5, the solution treatment is a secondary solution treatment, which is carried out at 490-510°C for 2h-5h and then at 510-540°C for 5h-10h.
[0019] Furthermore, in step S5, the aging treatment temperature is 150-180° C., and the insulation time is 3 h-8 h.
[0020] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0021] 1. Compared with the existing aluminum-magnesium-copper alloy, the aluminum-copper-magnesium alloy of the present invention introduces a higher concentration of Mg element. The industry average cost of raw magnesium smelting is about 19,000 yuan / ton, which can significantly reduce the alloy addition cost. At the same time, the relative density of Mg element is only 1.74g / cm3, which has a significant lightweight advantage.
[0022] 2. The aluminum-copper-magnesium alloy of the present invention has a reasonable alloy composition design and precise preparation process parameter control, so that the prepared aluminum-copper-magnesium alloy has a low cost and good mechanical properties at room temperature and 300°C. The present invention can significantly promote the formation of Al2Cu(Ω) high-temperature stable phase by increasing the Mg element concentration so that the Cu / Mg mass ratio is between 2 and 4, ensuring that the alloy still has high strength at 300°C; introduce Mn and Zr elements to reduce the diffusion rate of Cu element in the matrix Al, delay the precipitation process of aluminum-copper supersaturated solid solution at high temperature, and ensure that the alloy has higher mechanical properties at high temperature; add Ti, Sc and other refinement elements to play a role in fine grain strengthening, and at the same time, the rare earth Sc element is enriched at the grain boundary with Al, Cu, Mn, etc. to form refractory stable intermetallic compounds, which are distributed along the grains and dendrites to form a hard skeleton, effectively hindering grain boundary sliding and creep deformation at room temperature and high temperature, and further improving the room temperature and high temperature mechanical properties of the alloy. The present invention fully dissolves the cast Al2Cu precipitation phase into the matrix through a two-stage solid solution process; controls the dispersion precipitation of the Al2Cu(Ω) high-temperature stable phase through an aging heat treatment process, and further improves the room temperature and high-temperature mechanical properties of the alloy.
[0023] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0025] Figure 1 The as-cast microstructure diagram of the high-strength and heat-resistant aluminum-copper-magnesium alloy prepared in Example 1 of the present invention;
[0026] Figure 2 This is a heat-treated microstructure diagram of the high-strength and heat-resistant aluminum-copper-magnesium alloy prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.
[0028] The invention provides a high-strength heat-resistant aluminum-copper-magnesium alloy, whose components are as follows by mass percentage: Cu: 4.5-5.5%, Mg: 1.5-2.5%, Mn: 0.2-1.0%, Ti: 0.1-0.5%, Zr: 0.1-0.5%, Sc: 0.1-0.5%; Fe: 0-0.1%; the balance is aluminum and inevitable impurities.
[0029] Among them, the mass ratio of Cu / Mg is 2 to 4, which can improve the room temperature and high temperature mechanical properties of the alloy; illustratively, the mass ratio of Cu / Mg is 2.20, 2.40, 2.60, 2.70, 2.80, 2.90, 3.00, 3.10, 3.20, 3.30, 3.40, 3.50, 3.60, 3.70, 3.80, and 3.90.
[0030] The reasons for limiting the composition of the ingot of the high-strength and heat-resistant aluminum-copper-magnesium alloy and the method for producing the same in the present invention are explained below. The mass percentage in the composition is expressed only in %.
[0031] Cu: forms Al2Cu(θ) strengthening phase, improves room temperature and high temperature strength. If the Cu content is too high, hot cracking defects are prone to occur in the casting. In the present invention, the Cu content is 4.5-5.5%;
[0032] Mg: promotes the formation of Al2Cu(Ω) high temperature stable phase and increases high temperature strength. Too much Mg addition will reduce the casting fluidity of the alloy and also introduce oxide inclusions. In the present invention, the Mg content is 1.5-2.5%;
[0033] Mn: reduces the diffusion rate of Cu element in the matrix Al, delays the precipitation process of the supersaturated solid solution of aluminum and copper at high temperature, and ensures that the alloy has higher mechanical properties at high temperature; in the present invention, the content of Mn is 0.2-1.0%;
[0034] Ti: refines grains, reduces the distance between dendrite arms, and exerts a fine grain strengthening effect; in the present invention, the content of Ti is 0.1-0.5%;
[0035] Zr: together with Mn, is used to reduce the diffusion rate of Cu in the matrix Al, delay the precipitation process of the supersaturated solid solution of aluminum and copper at high temperature, and ensure that the alloy has higher mechanical properties at high temperature; in the present invention, the content of Zr is 0.1-0.5%;
[0036] Sc: plays a role in grain refinement and strengthening. At the same time, the rare earth Sc element is enriched at the grain boundary and forms refractory and stable intermetallic compounds with Al, Cu, Mn, etc., distributed along the grains and dendrites, forming a hard skeleton, effectively hindering grain boundary sliding and creep deformation at room temperature and high temperature, and further improving the room temperature and high temperature mechanical properties of the alloy; in the present invention, the content of Sc is 0.1-0.5%;
[0037] Fe: It is beneficial for alloy demoulding. A content of Fe greater than 0.1% will significantly reduce the mechanical properties of the alloy and needs to be strictly controlled. In the present invention, the content of Fe is 0 to 0.1%.
[0038] Preferably, a high-strength and heat-resistant aluminum-copper-magnesium alloy, whose components, by mass percentage, are: Cu: 4.5-5.40%, Mg: 1.5-2.40%, Mn: 0.2-0.90%, Ti: 0.1-0.40%, Zr: 0.1-0.40%, Sc: 0.1-0.40%; Fe: 0-0.09%; the remainder is aluminum and unavoidable impurities.
[0039] Preferably, a high-strength and heat-resistant aluminum-copper-magnesium alloy has the following components in percentage by mass: Cu: 4.55-5.35%, Mg: 1.55-2.35%, Mn: 0.25-0.85%, Ti: 0.15-0.35%, Zr: 0.15-0.35%, Sc: 0.15-0.35%; Fe: 0.005-0.085%; the remainder is aluminum and unavoidable impurities.
[0040] Preferably, a high-strength and heat-resistant aluminum-copper-magnesium alloy, whose components, by mass percentage, are: Cu: 4.6-5.30%, Mg: 1.6-2.30%, Mn: 0.3-0.80%, Ti: 0.18-0.30%, Zr: 0.18-0.30%, Sc: 0.18-0.30%; Fe: 0.01-0.08%; the remainder is aluminum and unavoidable impurities.
[0041] Preferably, a high-strength and heat-resistant aluminum-copper-magnesium alloy, whose components, by mass percentage, are: Cu: 4.66-5.25%, Mg: 1.66-2.25%, Mn: 0.34-0.75%, Ti: 0.21-0.28%, Zr: 0.19-0.25%, Sc: 0.19-0.25%; Fe: 0.015-0.075%; the remainder is aluminum and unavoidable impurities.
[0042] Preferably, a high-strength and heat-resistant aluminum-copper-magnesium alloy, whose components, by mass percentage, are: Cu: 4.70-5.20%, Mg: 1.70-2.20%, Mn: 0.42-0.70%, Ti: 0.23-0.26%, Zr: 0.20-0.23%, Sc: 0.20-0.24%; Fe: 0.02-0.06%; the remainder is aluminum and unavoidable impurities.
[0043] Preferably, a high-strength and heat-resistant aluminum-copper-magnesium alloy, whose components, in terms of mass percentage, are: Cu: 4.73-5.15%, Mg: 1.75-2.15%, Mn: 0.53-0.65%, Ti: 0.19-0.25%, Zr: 0.19-0.22%, Sc: 0.21-0.23%; Fe: 0.025-0.055%; the remainder is aluminum and unavoidable impurities.
[0044] Preferably, a high-strength and heat-resistant aluminum-copper-magnesium alloy has the following components in percentage by mass: Cu: 4.86-5.10%, Mg: 1.83-2.10%, Mn: 0.2-0.60%, Ti: 0.1-0.16%, Zr: 0.1-0.16%, Sc: 0.1-0.16%; Fe: 0.03-0.05%; the remainder is aluminum and unavoidable impurities.
[0045] Preferably, a high-strength and heat-resistant aluminum-copper-magnesium alloy has the following components in percentage by mass: Cu: 4.5-5.05%, Mg: 1.5-2.05%, Mn: 0.2-0.55%, Ti: 0.1-0.15%, Zr: 0.1-0.15%, Sc: 0.1-0.15%; Fe: 0.035-0.045%; the remainder is aluminum and unavoidable impurities.
[0046] Preferably, a high-strength and heat-resistant aluminum-copper-magnesium alloy, whose components, by mass percentage, are: Cu: 4.6-5.00%, Mg: 1.6-2.0%, Mn: 0.2-0.50%, Ti: 0.1-0.13%, Zr: 0.1-0.13%, Sc: 0.1-0.13%; Fe: 0.037-0.04%; the remainder is aluminum and unavoidable impurities.
[0047] Preferably, a high-strength and heat-resistant aluminum-copper-magnesium alloy, whose components, by mass percentage, are: Cu: 4.94-5.12%, Mg: 1.84-2.32%, Mn: 0.41-0.79%, Ti: 0.1-0.25%, Zr: 0.15-0.22%, Sc: 0.3-0.33%; Fe: 0.043-0.08%; the remainder is aluminum and unavoidable impurities.
[0048] Preferably, the mass ratio of Cu / Mg is 2.20 to 2.68, such as 2.21, 2.22, 2.23, 2.24, 2.25, 2.26, 2.27, 2.28, 2.29, 2.30, 2.31, 2.32, 2.33, 2.34, 2.35, 2.36, 2.37, 2.38, 2.39, 2.40, 2.41, 2.42, 2.43, 2.44, 2.45, 2.46, 2.47, 2.48, 2.49, 2.50, 2.51, 2.52, 2.53, 2.54, 2.55, 2.56, 2.57, 2.58, 2.59, 2.60, 2.61, 2.62, 2.63, 2.64, 2.65, 2.66, 2.67.
[0049] The present invention also provides a preparation method of the above-mentioned high-strength and heat-resistant aluminum-copper-magnesium alloy, comprising separately adding a pure Mg block during the preparation process, degassing, standing and heat treatment during the refining process; the melting temperature when the pure Mg block is added is lower than the melting temperature of the remaining raw materials, generally 700-730°C; the standing time during the refining process is 20-30 minutes; the heat treatment is a secondary solution treatment and an aging treatment, the solution treatment is to keep warm at 490-510°C for 2h-5h, then keep warm at 510-540°C for 5h-10h, and then quench and then perform an aging treatment at 150-180°C for 3h-8h.
[0050] The present invention also provides a method for preparing the above-mentioned high-strength heat-resistant aluminum-copper-magnesium alloy, comprising the following steps:
[0051] S1: According to the mass percentage of each element, pure Al, pure Mg, Al-Mn master alloy, Al-Cu master alloy, Al-Ti master alloy, Al-Zr master alloy, and Al-Sc master alloy are weighed as raw materials respectively;
[0052] S2: Smelting starts, adding pure aluminum ingots, Al-Mn master alloys, and Al-Cu master alloys to the resistance furnace, and keeping them warm at the first smelting temperature. After they are molten, Al-Ti master alloys, Al-Zr master alloys, and Al-Sc master alloys are added to continue smelting at the first smelting temperature, and keeping warm. After the temperature drops to the second smelting temperature, a pure magnesium block is pressed in with a pressing spoon;
[0053] S3: After all the alloy elements are added, refining and degassing are carried out, standing and slag removal is carried out;
[0054] S4: casting;
[0055] S5: subjecting the cast alloy to solid solution and aging treatment to obtain a finished alloy product.
[0056] Specifically, in step S1, pure Al, pure Mg, Al-Mn master alloy, Al-Cu master alloy, Al-Ti master alloy, Al-Zr master alloy, and Al-Sc master alloy are weighed as raw materials according to the mass percentage of each element.
[0057] Specifically, in step S2, at the beginning of smelting, pure aluminum ingots, Al-Mn master alloys, and Al-Cu master alloys are added to the resistance furnace, and the first smelting temperature is 750-800°C, which is kept warm for 30-60 minutes. Smelting at this temperature is conducive to the full dissolution of the master alloy elements and improves the smelting efficiency. After the pure aluminum ingots, Al-Mn master alloys, and Al-Cu master alloys are cleared, Al-Ti master alloys, Al-Zr master alloys, and Al-Sc master alloys are added and continue to be smelted at 750-800°C. After they are completely melted, they are kept warm for 30-60 minutes, and then after the temperature drops to the second smelting temperature of 700-730°C, a pure magnesium block is pressed in with a pressing spoon. The lower smelting temperature is conducive to reducing the burn-out of the Mg element.
[0058] Specifically, in step S3, after all the alloy elements are added, refining and degassing are carried out, and the mixture is allowed to stand for 20-30 minutes, and slag is removed; the gas used for refining and degassing is preferably an inert gas such as nitrogen or argon, and the degassing is carried out by rotating spraying throughout the whole process.
[0059] Specifically, the casting process is gravity or low-pressure casting, the pouring temperature is 670-690°C, and the mold insulation temperature is 150-200°C. The lower pouring temperature can reduce the burning of magnesium, increase the solidification supercooling, thereby increasing the driving force of tissue nucleation, and refine the grain size; mold insulation within a certain range can ensure the complete filling of the casting and improve the surface quality of the casting. Too low mold temperature will lead to product molding difficulties, weld lines and defects such as rough product surface; too high mold temperature will easily lead to surface bubbles, sticking mold, shrinkage holes and other defects, and the mold is easy to deform.
[0060] Specifically, in step S5, the solution treatment is a secondary solution treatment, which is kept at 490-510°C for 2h-5h, then kept at 510-540°C for 5h-10h, and then quenched and aged at 150-180°C for 3h-8h.
[0061] The aluminum-copper-magnesium alloy of the present invention reduces the cost of the prepared aluminum-copper-magnesium alloy through reasonable alloy composition design and precise preparation process parameter control, and has good mechanical properties at room temperature and high temperature of 300°C. The present invention can significantly promote the formation of Al2Cu(Ω) high temperature stable phase by increasing the Mg element concentration so that the Cu / Mg mass ratio is between 2 and 4, and ensure that the alloy still has high strength at a high temperature of 300°C; introduce Mn and Zr elements to reduce the diffusion rate of Cu element in the matrix Al, delay the precipitation process of aluminum-copper supersaturated solid solution at high temperature, and ensure that the alloy has higher mechanical properties at high temperature; add Ti, Sc and other refinement elements to exert fine grain strengthening, and at the same time, the rare earth Sc element is enriched at the grain boundary with Al, Cu, Mn and the like to form refractory stable intermetallic compounds, which are distributed along the grains and dendrites to form a hard skeleton, effectively hindering grain boundary sliding and creep deformation at room temperature and high temperature, and further improving the room temperature and high temperature mechanical properties of the alloy. The present invention fully dissolves the cast Al2Cu precipitation phase into the matrix through a two-stage solid solution process; controls the dispersion precipitation of the Al2Cu(Ω) high-temperature stable phase through an aging heat treatment process, and further improves the room temperature and high-temperature mechanical properties of the alloy.
[0062] The main matrix of the cast structure of the aluminum-copper-magnesium alloy prepared by the above preparation method is primary α-Al, and white Al2Cu and Al2CuMg phases and some Sc-rich intermetallic phases are precipitated at the grain boundaries, and the area fraction of the precipitated phases at the grain boundaries accounts for about 10-20%. After heat treatment, the Al2Cu and Al2CuMg phases at the grain boundaries are basically dissolved in the matrix, and the Al2Cu(Ω) high-temperature stable phase is dispersed and precipitated in the aging state.
[0063] It should be noted that most of the existing aluminum-copper-magnesium alloys promote the formation of Al2Cu high-temperature stable phase Ω by adding Ag elements. The Ag element has a high addition cost, which increases the preparation cost of the alloy. Compared with the existing aluminum-copper-magnesium alloys, the method of the present invention introduces a higher concentration of Mg elements. The industry average cost of raw magnesium smelting is about 19,000 yuan / ton, which can significantly reduce the preparation cost of aluminum-copper-magnesium alloys. At the same time, the relative density of Mg elements is only 1.74g / cm3, which has a significant lightweight advantage.
[0064] The aluminum-copper-magnesium alloy prepared by the present invention has high mechanical properties at both room temperature and high temperature of 300°C; at room temperature, the yield strength of the aluminum-copper-magnesium alloy prepared by the present invention is ≥280Mpa (such as 282-295MPa), the tensile strength is ≥400MPa (such as 412-430MPa), and the elongation is ≥8% (such as 8.0-8.2%); at a high temperature of 300°C, the yield strength of the aluminum-copper-magnesium alloy prepared by the present invention is ≥120Mpa (such as 120-130MPa), the tensile strength is ≥150MPa (such as 155-165MPa), and the elongation is ≥13% (such as 13.0-13.2%)
[0065] The advantages of the precise control of the chemical composition, content and preparation process parameters of the present invention will be demonstrated below with specific examples.
[0066] Example 1
[0067] The high-strength heat-resistant aluminum-copper-magnesium alloy of this embodiment has the following components by mass percentage: Cu: 4.94%, Mg: 1.84%, Mn: 0.79%, Ti: 0.1%, Zr: 0.22%, Sc: 0.33%; Fe: 0.08%; the remainder is aluminum and unavoidable impurities;
[0068] The mass ratio of Cu / Mg is 2.68.
[0069] The method for preparing the above-mentioned high-strength heat-resistant aluminum-copper-magnesium alloy comprises the following steps:
[0070] S1: According to the mass percentage of each element, weigh pure Al, pure Mg, Al-Mn master alloy, Al-Cu master alloy, Al-Ti master alloy, Al-Zr master alloy, and Al-Sc master alloy, a total of 30 kg as raw materials;
[0071] S2: At the beginning of smelting, pure aluminum ingots, Al-Mn master alloys, and Al-Cu master alloys are added to the resistance furnace and kept at the first smelting temperature of 750°C for 40 minutes. After being molten, Al-Ti master alloys, Al-Zr master alloys, and Al-Sc master alloys are added and continued to be smelted at 750°C. After being completely melted, they are kept at this temperature for 40 minutes. After the temperature drops to the second smelting temperature of 730°C, a pure magnesium block is pressed in with a pressing spoon;
[0072] S3: After adding all the alloy elements, refining and degassing are carried out, standing for 20 minutes, and slag removal;
[0073] S4: gravity casting, pouring at 690℃, mold temperature kept at 150℃;
[0074] S5: subjecting the cast alloy to solid solution and aging treatment to obtain a finished alloy product.
[0075] The solution treatment is a two-stage solution treatment, which is kept at 500°C for 4 hours, then kept at 520°C for 6 hours, and then aged after quenching at 160°C for 8 hours.
[0076] The aluminum-copper-magnesium alloy prepared in this embodiment has a room temperature yield strength of 282 MPa, a tensile strength of 412 MPa, and an elongation of 8.0%; a yield strength of 120 MPa, a tensile strength of 155 MPa, and an elongation of 13% at 300°C.
[0077] Example 2
[0078] The high-strength heat-resistant aluminum-copper-magnesium alloy of this embodiment has the following components by mass percentage: Cu: 5.12%, Mg: 2.32%, Mn: 0.41%, Ti: 0.25%, Zr: 0.15%, Sc: 0.30%; Fe: 0.08%; the remainder is aluminum and unavoidable impurities;
[0079] The mass ratio of Cu / Mg is 2.21.
[0080] The method for preparing the above-mentioned high-strength heat-resistant aluminum-copper-magnesium alloy comprises the following steps:
[0081] S1: According to the mass percentage of each element, weigh pure Al, pure Mg, Al-Mn master alloy, Al-Cu master alloy, Al-Ti master alloy, Al-Zr master alloy, and Al-Sc master alloy, a total of 30 kg as raw materials;
[0082] S2: At the beginning of smelting, pure aluminum ingots, Al-Mn master alloys, and Al-Cu master alloys are added to the resistance furnace and kept at the first smelting temperature of 780°C for 30 minutes. After being molten, Al-Ti master alloys, Al-Zr master alloys, and Al-Sc master alloys are added and continued to be smelted at 780°C. After being completely melted, they are kept at this temperature for 30 minutes. After the temperature drops to the second smelting temperature of 710°C, a pure magnesium block is pressed in with a pressing spoon;
[0083] S3: After adding all the alloy elements, they are refined and degassed, left to stand for 30 minutes, slag removed, and poured;
[0084] S4: Gravity casting; pouring at 670℃, mold temperature kept at 180℃;
[0085] S5: subjecting the cast alloy to solid solution and aging treatment to obtain a finished alloy product.
[0086] The solution treatment is a two-stage solution treatment, which is kept at 510°C for 3 hours, then kept at 520°C for 8 hours, and then aged after quenching at 175°C for 5 hours.
[0087] The aluminum-copper-magnesium alloy prepared in this embodiment has a room temperature yield strength of 295 MPa, a tensile strength of 430 MPa, and an elongation of 8.2%; a yield strength of 130 MPa, a tensile strength of 165 MPa, and an elongation of 13.2% at 300°C.
[0088] Comparative Example 1
[0089] The high-strength heat-resistant aluminum-copper-magnesium alloy of this comparative example has the following components by mass percentage: Cu: 4.26%, Mg: 0.34%, Mn: 0.4%, Ti: 0.25%, Zr: 0.15%, Sc: 0.31%; Fe: 0.06%; the balance is aluminum and unavoidable impurities;
[0090] The mass ratio of Cu / Mg is 12.53.
[0091] The method for preparing the above-mentioned high-strength heat-resistant aluminum-copper-magnesium alloy comprises the following steps:
[0092] S1: According to the mass percentage of each element, weigh pure Al, pure Mg, Al-Mn master alloy, Al-Cu master alloy, Al-Ti master alloy, Al-Zr master alloy, and Al-Sc master alloy, a total of 30 kg as raw materials;
[0093] S2: At the beginning of smelting, pure aluminum ingots, Al-Mn master alloys, and Al-Cu master alloys are added to the resistance furnace and kept at the first smelting temperature of 780°C for 20 minutes. After being molten, Al-Ti master alloys, Al-Zr master alloys, and Al-Sc master alloys are added and continued to be smelted at 780°C. After being completely melted, they are kept at this temperature for 20 minutes. After the temperature drops to the second smelting temperature of 730°C, a pure magnesium block is pressed in with a pressing spoon;
[0094] S3: After adding all the alloy elements, refining and degassing are carried out, standing for 30 minutes, and slag removal;
[0095] S4: gravity casting, pouring at 670℃, mold temperature kept at 150℃;
[0096] S5: subjecting the cast alloy to solid solution and aging treatment to obtain a finished alloy product.
[0097] The solution treatment is a two-stage solution treatment, which is kept at 500°C for 4 hours, then kept at 520°C for 6 hours, and then aged after quenching at 175°C for 5 hours.
[0098] The aluminum-copper-magnesium alloy prepared in this comparative example has a room temperature yield strength of 191 MPa, a tensile strength of 323 MPa, and an elongation of 8.5%; a yield strength of 94 MPa, a tensile strength of 117 MPa, and an elongation of 15% at 300°C.
[0099] Comparative Example 2
[0100] The high-strength heat-resistant aluminum-copper-magnesium alloy of this comparative example has the following components by mass percentage: Cu: 6.13%, Mg: 0.31%, Mn: 0.42%, Ti: 0.26%, Zr: 0.15%, Sc: 0.30%; Fe: 0.06%; the balance is aluminum and unavoidable impurities;
[0101] The mass ratio of Cu / Mg is 19.77.
[0102] The method for preparing the above-mentioned high-strength heat-resistant aluminum-copper-magnesium alloy comprises the following steps:
[0103] S1: According to the mass percentage of each element, weigh pure Al, pure Mg, Al-Mn master alloy, Al-Cu master alloy, Al-Ti master alloy, Al-Zr master alloy, and Al-Sc master alloy, a total of 30 kg as raw materials;
[0104] S2: At the beginning of smelting, pure aluminum ingots, Al-Mn master alloys, and Al-Cu master alloys are added to the resistance furnace and kept at the first smelting temperature of 750°C for 30 minutes. After they are completely melted, Al-Ti master alloys, Al-Zr master alloys, and Al-Sc master alloys are added and continued to be smelted at 750°C. After they are completely melted, they are kept at this temperature for 30 minutes. After the temperature drops to the second smelting temperature of 730°C, a pure magnesium block is pressed in with a pressing spoon;
[0105] S3: After adding all the alloy elements, they are refined and degassed, left to stand for 30 minutes, slag removed, and poured;
[0106] S4: Gravity casting; pouring at 690℃, mold temperature kept at 150℃;
[0107] S5: subjecting the cast alloy to solid solution and aging treatment to obtain a finished alloy product.
[0108] The solution treatment is a two-stage solution treatment, which is kept at 500°C for 4 hours, then kept at 520°C for 6 hours, and then aged after quenching at 175°C for 5 hours.
[0109] The aluminum-copper-magnesium alloy prepared in this comparative example has a room-temperature yield strength of 312 MPa, a tensile strength of 352 MPa, and an elongation of 9.0%; a yield strength of 117 MPa, a tensile strength of 140 MPa, and an elongation of 14% at 300°C.
[0110] Comparative Example 3
[0111] The high-strength heat-resistant aluminum-copper-magnesium alloy of this comparative example has the following components by mass percentage: Cu: 4.87%, Mg: 1.03%, Mn: 0.41%, Ti: 0.27%, Zr: 0.15%, Sc: 0.30%; Fe: 0.05%; the balance is aluminum and unavoidable impurities;
[0112] The mass ratio of Cu / Mg is 4.73.
[0113] The method for preparing the above-mentioned high-strength heat-resistant aluminum-copper-magnesium alloy comprises the following steps:
[0114] S1: According to the mass percentage of each element, weigh pure Al, pure Mg, Al-Mn master alloy, Al-Cu master alloy, Al-Ti master alloy, Al-Zr master alloy, and Al-Sc master alloy, a total of 30 kg as raw materials;
[0115] S2: At the beginning of smelting, pure aluminum ingots, Al-Mn master alloys, and Al-Cu master alloys are added to the resistance furnace and kept at the first smelting temperature of 780°C for 30 minutes. After being molten, Al-Ti master alloys, Al-Zr master alloys, and Al-Sc master alloys are added and continued to be smelted at 780°C. After being completely melted, they are kept at this temperature for 30 minutes. After the temperature drops to the second smelting temperature of 710°C, a pure magnesium block is pressed in with a pressing spoon;
[0116] S3: After adding all the alloy elements, refining and degassing are carried out, standing for 30 minutes, and slag removal;
[0117] S4: Gravity casting; pouring at 670℃, mold temperature kept at 180℃;
[0118] S5: subjecting the cast alloy to solid solution and aging treatment to obtain a finished alloy product.
[0119] The solution treatment is a two-stage solution treatment, which is kept at 500°C for 4 hours, then kept at 520°C for 6 hours, and then aged after quenching at 175°C for 5 hours.
[0120] The aluminum-copper-magnesium alloy prepared in this comparative example has a room-temperature yield strength of 225 MPa, a tensile strength of 338 MPa, and an elongation of 8.0%; a yield strength of 121 MPa, a tensile strength of 141 MPa, and an elongation of 10.0% at 300°C.
[0121] Comparative Example 4
[0122] The high-strength heat-resistant aluminum-copper-magnesium alloy of this comparative example has the following components by mass percentage: Cu: 5.0%, Mg: 1.87%, Mn: 0.43%, Ti: 0.36%, Zr: 0.15%, Sc: 0.30%; Fe: 0.5%; the balance is aluminum and unavoidable impurities;
[0123] The mass ratio of Cu / Mg is 2.67.
[0124] The method for preparing the above-mentioned high-strength heat-resistant aluminum-copper-magnesium alloy comprises the following steps:
[0125] S1: According to the mass percentage of each element, weigh pure Al, pure Mg, Al-Mn master alloy, Al-Cu master alloy, Al-Ti master alloy, Al-Zr master alloy, and Al-Sc master alloy, a total of 30 kg as raw materials;
[0126] S2: At the beginning of smelting, pure aluminum ingots, Al-Mn master alloys, and Al-Cu master alloys are added to the resistance furnace and kept at the first smelting temperature of 780°C for 30 minutes. After being molten, Al-Ti master alloys, Al-Zr master alloys, and Al-Sc master alloys are added and continued to be smelted at 780°C. After being completely melted, they are kept at this temperature for 30 minutes. After the temperature drops to the second smelting temperature of 710°C, a pure magnesium block is pressed in with a pressing spoon;
[0127] S3: After adding all the alloy elements, refining and degassing are carried out, standing for 30 minutes, and slag removal;
[0128] S4: Gravity casting; pouring at 670℃, mold temperature kept at 150℃;
[0129] S5: subjecting the cast alloy to solid solution and aging treatment to obtain a finished alloy product.
[0130] The solution treatment is a two-stage solution treatment, which is kept at 500°C for 4 hours, then kept at 520°C for 6 hours, and then aged after quenching at 175°C for 5 hours.
[0131] The aluminum-copper-magnesium alloy prepared in this comparative example has a room temperature yield strength of 210 MPa, a tensile strength of 300 MPa, and an elongation of 4.0%; a yield strength of 110 MPa, a tensile strength of 125 MPa, and an elongation of 7.0% at 300°C.
[0132] Comparative Example 5
[0133] The high-strength heat-resistant aluminum-copper-magnesium alloy of this comparative example has the following components by mass percentage: Cu: 4.94%, Mg: 1.84%, Mn: 0.79%, Ti: 0.1%, Zr: 0.22%, Sc: 0.33%; Fe: 0.08%; the balance is aluminum and unavoidable impurities;
[0134] The mass ratio of Cu / Mg is 2.68.
[0135] The method for preparing the above-mentioned high-strength heat-resistant aluminum-copper-magnesium alloy comprises the following steps:
[0136] S1: According to the mass percentage of each element, weigh pure Al, pure Mg, Al-Mn master alloy, Al-Cu master alloy, Al-Ti master alloy, Al-Zr master alloy, and Al-Sc master alloy, a total of 30 kg as raw materials;
[0137] S2: At the beginning of smelting, pure aluminum ingots, Al-Mn master alloys, and Al-Cu master alloys are added to the resistance furnace and kept at the first smelting temperature of 750°C for 30 minutes. After they are completely melted, Al-Ti master alloys, Al-Zr master alloys, and Al-Sc master alloys are added and continued to be smelted at 750°C. After they are completely melted, they are kept at this temperature for 30 minutes. After the temperature drops to the second smelting temperature of 730°C, a pure magnesium block is pressed in with a pressing spoon;
[0138] S3: After adding all the alloy elements, refining and degassing are carried out, standing for 20 minutes, and slag removal;
[0139] S4: Gravity casting; pouring at 670℃, mold temperature kept at 150℃;
[0140] S5: subjecting the cast alloy to solid solution and aging treatment to obtain a finished alloy product.
[0141] Among them, the solid solution treatment is a secondary solid solution treatment, which is kept at 470°C for 2 hours, then kept at 480°C for 8 hours, and then quenched and aged at 170°C for 18 hours.
[0142] The aluminum-copper-magnesium alloy prepared in this comparative example has a room-temperature yield strength of 273 MPa, a tensile strength of 323 MPa, and an elongation of 2.5%; a yield strength of 114 MPa, a tensile strength of 116 MPa, and an elongation of 10% at 300°C.
[0143] Comparative Example 6
[0144] The high-strength heat-resistant aluminum-copper-magnesium alloy of this comparative example has the following components by mass percentage: Cu: 5.0%, Mg: 1.80%, Mn: 0.61%, Ti: 0.3%, Zr: 0.30%, Sc: 0.33%; Fe: 0.10%; the balance is aluminum and unavoidable impurities;
[0145] The mass ratio of Cu / Mg is 2.78.
[0146] The method for preparing the above-mentioned high-strength heat-resistant aluminum-copper-magnesium alloy comprises the following steps:
[0147] S1: According to the mass percentage of each element, weigh pure Al, pure Mg, Al-Mn master alloy, Al-Cu master alloy, Al-Ti master alloy, Al-Zr master alloy, and Al-Sc master alloy, a total of 30 kg as raw materials;
[0148] S2: At the beginning of smelting, pure aluminum ingots, Al-Mn master alloys, and Al-Cu master alloys are added to the resistance furnace and smelted at the first smelting temperature of 780°C for 30 minutes. After being molten, Al-Ti master alloys, Al-Zr master alloys, and Al-Sc master alloys are added and smelted at 780°C. After being completely melted, the alloys are kept warm for 30 minutes. At the second smelting temperature of 780°C, pure magnesium blocks are pressed in with a pressing spoon;
[0149] S3: After adding all the alloy elements, refining and degassing are carried out, standing for 60 minutes, and slag removal;
[0150] S4: Gravity casting, pouring at 730℃, mold temperature kept at 150℃;
[0151] S5: subjecting the cast alloy to solid solution and aging treatment to obtain a finished alloy product.
[0152] The solution treatment is a two-stage solution treatment, which is kept at 500°C for 4 hours, then kept at 520°C for 6 hours, and then aged after quenching at 175°C for 5 hours.
[0153] The aluminum-copper-magnesium alloy prepared in this embodiment has a room temperature yield strength of 262 MPa, a tensile strength of 380 MPa, and an elongation of 7.0%; a yield strength of 105 MPa, a tensile strength of 128 MPa, and an elongation of 12% at 300°C.
[0154] Table 1 Chemical composition of the alloys of the embodiments and comparative examples (wt, %)
[0155] serial number Cu Mg Mn Ti Zr Sc Fe Example 1 4.94 1.84 0.79 0.10 0.22 0.33 0.08 Example 2 5.12 2.32 0.41 0.25 0.15 0.30 0.08 Comparative Example 1 4.26 0.34 0.40 0.25 0.15 0.31 0.06 Comparative Example 2 6.13 0.31 0.42 0.26 0.15 0.30 0.06 Comparative Example 3 4.87 1.03 0.41 0.27 0.15 0.30 0.05 Comparative Example 4 5.0 1.87 0.43 0.36 0.15 0.30 0.5 Comparative Example 5 4.94 1.84 0.79 0.10 0.22 0.33 0.08 Comparative Example 6 5.0 1.8 0.61 0.3 0.3 0.33 0.1
[0156] Table 2 Preparation process of alloys in Examples and Comparative Examples
[0157]
[0158]
[0159] Table 3 Mechanical properties of the alloys of the embodiments and comparative examples
[0160]
[0161] It can be seen from the comparative examples and embodiments that the alloy element composition or content of comparative examples 1-4 does not meet the requirements of the present invention, wherein the addition amounts of Cu and Mg in comparative examples 1-3 do not meet the requirements of the present invention, excessive Fe element is added in comparative example 4, the heat treatment system of comparative example 5 does not meet the requirements of the present invention, and excessively high addition temperature and excessively long standing time are used in the process of adding Mg in comparative example 6. As a result, the yield strength, tensile strength and elongation of the castings in the cast and heat-treated states are reduced to varying degrees compared with the embodiments.
[0162] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A high-strength heat-resistant aluminum-copper-magnesium alloy, characterized in that: The alloy components are calculated by mass percentage as follows: Cu: 4.5-5.5%, Mg: 1.5-2.5%, Mn: 0.2-1.0%, Ti: 0.1-0.5%, Zr: 0.1-0.5%, Sc: 0.1-0.5%; Fe: 0-0.1%; the balance is aluminum and unavoidable impurities.
2. The aluminum-copper-magnesium alloy according to claim 1, characterized in that: The alloy components are calculated by mass percentage as follows: Cu: 4.94-5.12%, Mg: 1.84-2.32%, Mn: 0.41-0.79%, Ti: 0.1-0.25%, Zr: 0.15-0.22%, Sc: 0.3-0.33%; Fe: 0-0.08%; the remainder is aluminum and inevitable impurities.
3. The aluminum-copper-magnesium alloy according to claim 1, characterized in that: In the alloy component, the mass ratio of Cu / Mg is 2-4.
4. A method for preparing a high-strength heat-resistant aluminum-copper-magnesium alloy, used for preparing the aluminum-copper-magnesium alloy according to any one of claims 1 to 3, characterized in that: The steps include: S1: According to the mass percentage of each element, pure Al, pure Mg, Al-Mn master alloy, Al-Cu master alloy, Al-Ti master alloy, Al-Zr master alloy, and Al-Sc master alloy are weighed as raw materials respectively; S2: Smelting starts, adding pure aluminum ingots, Al-Mn master alloys, and Al-Cu master alloys to the resistance furnace, and keeping them warm at the first smelting temperature. After they are molten, Al-Ti master alloys, Al-Zr master alloys, and Al-Sc master alloys are added to continue smelting at the first smelting temperature, and keeping warm. After the temperature drops to the second smelting temperature, a pure magnesium block is pressed in with a pressing spoon; S3: After all the alloy elements are added, refining and degassing are carried out, standing and slag removal is carried out; S4: casting; S5: subjecting the cast alloy to solid solution and aging treatment to obtain a finished alloy product.
5. The preparation method according to claim 4, characterized in that: In step S2, the first smelting temperature is 750-800°C, and the holding time is 30-60 minutes.
6. The preparation method according to claim 5, characterized in that: In step S2, the second smelting temperature is 700-730°C.
7. The preparation method according to claim 6, characterized in that: In step S3, the step of standing is performed for 20-30 minutes.
8. The preparation method according to claim 7, characterized in that: In step S4, the casting process is gravity or low-pressure casting, the pouring temperature is 670-690°C, and the mold insulation temperature is 150-200°C.
9. The preparation method according to claim 8, characterized in that: In step S5, the solution treatment is a two-stage solution treatment, which is carried out at 490-510° C. for 2 h to 5 h, and then at 510-540° C. for 5 h to 10 h.
10. The preparation method according to claim 9, characterized in that: In step S5, the aging treatment temperature is 150-180°C, and the insulation time is 3h-8h.
Citation Information
Patent Citations
High strength and high heat resistant aluminum alloy material and preparation method thereof
CN104711468A
Sc-containing high-strength Al-Cu-Mg-Mn-Zr alloy and preparation method thereof
CN105441759A
Damage-resistant aluminum alloy and preparation method thereof
CN106609329A
Aluminum-copper-magnesium-series high-strength heat-resistant cast aluminum alloy and manufacturing method thereof
CN108342628A
Multi-element heat-resistant aluminum alloy and preparation method thereof
CN111101038A